Food Assistance Deserts in Central Florida: Identifying Service Gaps Using Spatial Analysis. (March 2021) - Curran, Emily; Armenia, Amy
Food assistance works to relieve food insecurity, a persistent problem in the United States disproportionately affecting marginalized communities. In this study, we take a closer look at geographical service gaps in food assistance using Geographic Information System (GIS) analysis to measure food assistance deserts, a term for areas where the nearest food assistance location is more than a mile away from the population centroid of a block group. By combining geographic data with data from the American Community Survey, we identified characteristics and predictors of food assistance deserts. Our results indicate that locations of food assistance in Central Florida are generally responsive to the needs of the community but are lacking in more affluent areas. This research was made possible through a partnership between our institution and Second Harvest Food Bank of Central Florida. The affordability and accessibility of this project should serve as a model for assessing spatial inequality in social service agencies through collaborative community-based research.